The relationship among psychological factors, teacher factors, and online learning effectiveness: The mediating role of student engagement - Zong, Xuan; Johar, Gapar Bin Md (Edelweiss Applied Science and Technology, 2025)
The effectiveness of online learning serves as a critical benchmark for evaluating the quality of online course learning. However, the factors influencing online learning effectiveness are multifaceted and complex. Drawing on existing literature, this study investigates the impact of psychological factors, teacher factors, and student engagement on online learning effectiveness. A quantitative causal-explanatory research design was adopted, with data collected via structured questionnaires. Structural equation modeling was utilized to analyze the mediating role of student engagement in the relationship between psychological factors, teacher factors, and online learning effectiveness. The findings indicate that both psychological factors and teacher factors significantly influence online learning effectiveness. Further validation through statistical analysis confirmed that student engagement plays a mediating role in the relationship between psychological factors, teacher-related factors, and online learning effectiveness. This study underscores the pivotal role of student engagement in enhancing online learning effectiveness. Based on these insights, several recommendations are proposed to improve college student engagement in online learning, aiming to provide theoretical support and practical guidance for advancing online education and fostering its sustainable development.